Cicada-MET: an efficient ecological monitoring protocol of cicada populations - Pons, Pere; Puig-Gironès, Roger; Tobella, Carles; Peiris, Andreu; Bas, Josep M. (Frontiers in Ecology and Evolution, 2023)
Cicadas are a fascinating group of insects that play an essential role in terrestrial ecosystems.Their long-lasting association with plant roots encourages their use as indicators of vegetation and soil integrity. Cicada-MET is a novel, standardized method for monitoring cicada populations by counting cicada exuviae (i.e., the skin of emerged nymphs), providing an effective and efficient means to study their distribution, abundance, and ecology. The method involves annual exuviae counts along transects and fixed plots sampled throughout the emergence season. We validated Cicada-MET using a database of 466 counts from 64 transects over 10 years and the sampling of 60 plots for one season. Methodological aspects tested included sampling speed, exuviae detectability in successive counts, exuviae loss due to weather, and cicada species detection performance using exuviae counts compared to auditory methods. Transects captured approximately 10% of the total number of emerged nymphs across one season, demonstrating the protocol's reliability in estimating emerging cicada population numbers. However, caution is needed when inferring densities for larger areas, separated from paths where transects are located. The standardized nature of Cicada-MET reduces spatial and temporal biases, allowing for interspecific comparisons and monitoring interannual variations in abundances and emergence timing. This method is well-suited for studying the impact of natural and anthropogenic disturbances. The high-resolution data obtained can be easily combined with environmental variables, enhancing the value of cicada data as bioindicators. In summary, Cicada-MET offers a versatile and efficient tool for monitoring cicada populations, with applications in ecological indication, conservation, and management. The adaptability of Cicada-MET to various research questions, spatial scales, and long-term approaches, along with its quantitative accuracy and ease of use, make it a valuable resource for researchers and practitioners working with cicadas and their associated ecosystems.